Individual pension information: Recommendations for the case of Spain based on the experiences of other countries - Regúlez-Castillo, Marta (2012)
The aim of this paper is to establish some basic guidelines to help draft the information letter sent to individual contributors should it be decided to use this model in the Spanish public pension system. With this end in mind and basing our work on the experiences of the most advanced countries in the field and the pioneering papers by Jackson (2005), Larsson et al. (2008) and Sunden (2009), we look into the concept of “individual pension information” and identify its most relevant characteristics. We then give a detailed description of two models, those in the United States and Sweden, and in particular look at how they are structured, what aspects could be improved and what their limitations are. Finally we make some recommendations of special interest for designing the model for Spain.